Effectiveness of a stepped-care programme of WHO psychological interventions in migrant populations resettled in Italy: Study protocol for the RESPOND randomized controlled trial - Purgato, Marianna; Turrini, Giulia; Tedeschi, Federico; Serra, Riccardo; Tarsitani, Lorenzo; Compri, Beatrice; Muriago, Giulia; Cadorin, Camilla; Ostuzzi, Giovanni; Nicaise, Pablo; Lorant, Vincent; Sijbrandij, Marit; et al. (Frontiers in Public Health, 2023)
Introduction: Migrant populations are exposed to a variety of stressors and potentially traumatic events. As a consequence, migration may increase vulnerability of individuals towards a worsening of subjective wellbeing, quality of life, and mental health, which, in turn, may increase the risk of developing mental health conditions. Against this background, we designed a stepped-care programme consisting of two scalable psychological interventions developed by the World Health Organization and locally adapted for migrant populations. The effectiveness and cost-effectiveness of this stepped-care programme will be assessed in terms of mental health outcomes, resilience, wellbeing, and costs to healthcare systems. Methods and analysis: We present the study protocol for a pragmatic randomized study with a parallel-group design that will enrol participants with a migrant background and elevated level of psychological distress. Participants will be randomized to care as usual only or to care a usual plus a guided self-help stress management guide (Doing What Matters in Times of Stress, DWM) and a five-session cognitive behavioural intervention (Problem Management Plus, PM+). Participants will self-report all measures at baseline before random allocation, two weeks after DWM delivery, one week after PM+ delivery and two months after PM+ delivery. All participants will receive a single-session of a support intervention, namely Psychological First Aid. We will include 212 participants. An intention-to-treat analysis using linear mixed models will be conducted to explore the programme’s effect on anxiety and depression symptoms, as measured by the Patient Health Questionnaire – Anxiety and Depression Scale summary score two months after PM+ delivery. Secondary outcomes include post-traumatic stress disorder symptoms, resilience, quality of life, resource utilisation, cost, and cost-effectiveness. Discussion: This study is the first randomized controlled trial that combines two World Health Organization psychological interventions tailored for migrant populations with an elevated level of psychological distress. The present study will make available DWM/PM+ packages adapted for remote delivery following a task-shifting approach, and will generate evidence to inform policy responses based on a more efficient use of resources for improving resilience, wellbeing and mental health.